Os efeitos do laser terapêutico na cartilagem articular em modelo experimental de osteoartrite induzida por transecção do ligamento cruzado anterior - Santos, Anderson Amaro dos (Universidade Federal de São Carlos, 2012)
Objective: The aim of this study was to evaluate the effects of laser therapy on the degeneratives modifications in articular cartilage after anterior cruciate ligament transection (ACLT). Methods: We used eighty-male rats (Wistar), distributed into four groups: intact, injury control, injury laser treated, at 50 J/cm2 and injury laser treated, at 10 J/cm2. Animals were distributed into 2 subgroups, with different periods of sacrifice 5 and 8 weeks post-surgery. The animals were submitted to the surgery to induce OA by anterior cruciate ligament transection. Laser treatment started 2 weeks after the surgery and it was performed for 15 and 30 sessions. A laser 685 nm, at 10 and 50 J/cm2, 30mW was used. Results: Initial signs of tissue degradation could be observed 5 weeks post- ACLT, with the decrease of proteoglycans concentration and increase of thickness in the CG. After 8 weeks post-surgery, analysis showed a progression in the degenerative process in the CG, revealed by the increase of cellullarity and higher TNF- α, IL1 and MMP-13 immunoexpression. Laser therapy was able of modulating some of the aspects related to the degradative process, such as biomodulation of the number of condrocyte proliferation, prevention of proteogycans loss and decrease of MMP-13 immunoexpression. Conclusion: This study showed that 685nm laser, especially at 10 J/cm2 prevented features related to the articular degenerative process in the knees of rats.
Keywords: Fisioterapia; Laserterapia; Cartilagem articular; Osteoartrite; Laser de baixa intensidade; Articular cartilage; Osteoarthritis and laser therapy; CIENCIAS DA SAUDE